2022
DOI: 10.4103/jfmpc.jfmpc_1387_21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anesthesia quality with three methods: “propofol + fentanyl” vs. “propofol + fentanyl + lidocaine” vs. “propofol + fentanyl + lidocaine + ketamine” in patients referred to the scoping ward

Abstract: Introduction: Toleration of the complexity and pain of interventions such as endoscopy and colonoscopy is highly difficult for patients. Considering the disagreement on the method of injection of propofol, this study was performed to evaluate the quality of anesthesia using the three methods of propofol + fentanyl, propofol + fentanyl + lidocaine, and propofol + fentanyl + lidocaine + ketamine. Methods: This one-way blind clinical trial study included 99 patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is crucial to note that in the Aminnejad et al study, the effects of KET were evaluated in conjunction with dexmedetomidine, rather than propofol, as in our investigation. Edalatkhah et al, in comparing 3 drug combinations for anesthesia for colonoscopy, showed that the use of propofol with FNT, KET, and LID was associated with a lower incidence of respiratory events (cough, apnea, need for jaw thrust) than was the use of propofol with FNT or propofol with FNT and LID [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to note that in the Aminnejad et al study, the effects of KET were evaluated in conjunction with dexmedetomidine, rather than propofol, as in our investigation. Edalatkhah et al, in comparing 3 drug combinations for anesthesia for colonoscopy, showed that the use of propofol with FNT, KET, and LID was associated with a lower incidence of respiratory events (cough, apnea, need for jaw thrust) than was the use of propofol with FNT or propofol with FNT and LID [ 36 ].…”
Section: Discussionmentioning
confidence: 99%